Pengurusan disiplin di sekolah-sekolah menengah di sekitar bandar Muar Johor - Alexander Tek, Isidora (2013)
Management of school discipline is one of the school management scopes, which often becomes the focus of parents, media and society in Malaysia. Therefore, this study focuses on the cause of problems in the management of school discipline, the role of parents in assisting the management of school discipline, the criteria that should be possessed before one is to be appointed as a discipline teacher, training required by the discipline teachers, and the role of school management in assisting the management of school discipline. The data was obtained through questionnaires and interviews. The data obtained were analyzed using SPSS software and data from interview had been analyzed using thematic procedure and conclusion. The study found that there were eight causes of problems in discipline management. The findings had also identified twelve important criteria, which a teacher should posses before been appointed as a discipline teacher. Besides, several aspects of training had been proposed to strengthen the roles of discipline teachers in school